2021
DOI: 10.2147/rmhp.s280567
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Prognostic Nutritional Index Value is Related to Postoperative Delirium in Elderly Patients After Noncardiac Surgery: A Retrospective Cohort Study

Abstract: Malnutrition has been considered as a risk factor for postoperative delirium (POD). The Prognostic Nutritional Index (PNI) is a validated tool for assessing nutritional status. This study aimed to investigate the association between preoperative PNI values and the occurrence of POD in elderly surgical patients. Methods: The retrospective cohort study included 361 elderly individuals who underwent noncardiac surgery between 2018 and 2019. Perioperative data were collected from the patients' medical records. PNI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 30 publications
3
25
0
Order By: Relevance
“…These two markers for recent alcohol intake can be detected in the blood for approximately 10 h after a small to moderate alcohol intake and up to 5 days after large and repeated alcohol intakes [67][68][69]. As the efficacy of these two tests has been demonstrated in multiple settings, it has been also suggested that EtG and EtS should be included in screening tests for injured or atrisk for alcohol abuse people (including pregnant women) to investigate the possible association between residual alcohol effects and injuries, and to verify alcohol abstinence in cases of substance-related disorders [72,73]. In the liver, ethanol is metabolized via oxidative and non-oxidative (less than 1%) ways.…”
Section: Alcohol Abuse Detectionmentioning
confidence: 99%
“…These two markers for recent alcohol intake can be detected in the blood for approximately 10 h after a small to moderate alcohol intake and up to 5 days after large and repeated alcohol intakes [67][68][69]. As the efficacy of these two tests has been demonstrated in multiple settings, it has been also suggested that EtG and EtS should be included in screening tests for injured or atrisk for alcohol abuse people (including pregnant women) to investigate the possible association between residual alcohol effects and injuries, and to verify alcohol abstinence in cases of substance-related disorders [72,73]. In the liver, ethanol is metabolized via oxidative and non-oxidative (less than 1%) ways.…”
Section: Alcohol Abuse Detectionmentioning
confidence: 99%
“… 31 PNI, an indicator representing patients’ nutritional and immune status, is not only verified its association with long-term prognosis, 17 but also involves in the development of POD after non-cardiac surgery. 32 A previous finding indicated that lower PNI could increase the likelihood of developing POD in colorectal surgery. 21 Interestingly, another study noted that there was no association between PNI and POD in abdominal surgery, which might be related to sample size, patient characteristics, types of surgery and diagnostic tools.…”
Section: Discussionmentioning
confidence: 97%
“…Our study reported that the incidence of postoperative delirium was 13.5% in placebo-treated patients and 5.6% in the rosuvastatin group, and the results were similar to those of a large number of previous studies[ 12 , 17 , 20 , 21 ]. Liu et al [ 22 ] performed a retrospective cohort study that included 361 elderly patients and reported that 19.9% of noncardiac surgery individuals developed postoperative delirium after surgery. Kant et al [ 23 ] also conducted a study on 413 patients and reported that the incidence of postoperative delirium was as high as 17%, and preoperative brain magnetic resonance imaging features may indicate a predisposition for developing delirium after major surgery.…”
Section: Discussionmentioning
confidence: 99%